Product Market Integration, Comparative Advantages and Labour Market Performance - Torben M. Andersen; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2003)
In a two-country model with trade driven by comparative advantages, it is considered how imperfectly competitive labour markets are affected by lower frictions in international goods trade. Easier goods trading is equivalent to increased mobility of employment across countries and thus a change in the trade-off between wages and employment faced by wage setters. While the effects of product market integration on the trade-off between wages and employment in general is ambiguous, it is shown that product market integration works like a general improvement in productivity via the specialization it allows through trade. Unambiguously, real wages and employment and welfare improve upon reductions in trade frictions, and therefore workers are better off irrespective of whether the market power of unions is enhanced or muted.
Keywords: J30; J50; F15; 330; trade frictions; wage formation; employment; welfare gains; Wirtschaftsunion; Komparativer Kostenvorteil; Marktintegration; Außenhandelseffekt; Lohnstruktur; Humankapital; Einkommensverteilung; Arbeitslosigkeit; Ungelernte Arbeitskraefte; Theorie